The Current BRICS Trade Barriers on EU's Exports - Ludmila Borta (CES Working Papers, 2013)
As a major trading power in the world, the European Union is an important trading partner for five emerging economies, namely Brazil, Russia, India, China and South Africa (the BRICS countries). The EU is particularly interested in protecting the interests of developing countries and supports the idea that trade can promote their economic growth and production capacity. The aim of this paper is to present the main trade barriers on the import of goods that are practised currently by BRICS nations, limiting the EU exporters' access on their markets. These barriers were reported to the European Commission which has the mission to take actions to solve this problem. The European Union considers that the trade barriers applied by these five countries are unjustified.
Keywords: F13; F51; F53; 330; EU's exports; BRICS countries; trading partners; trade barriers; market access Romania